Citrus tristeza virus p20 suppresses antiviral RNA silencing by co-opting autophagy-related protein 8 to mediate the autophagic degradation of SGS3. - Yongle Zhang; Zuokun Yang; Zhe Zhang; Guoping Wang; Xiang-Dong Li; Ni Hong (PLoS Pathogens)
Viruses exploit autophagy to degrade host immune components for their successful infection. However, how viral factors sequester the autophagic substrates into autophagosomes remains largely unknown. In this study, we showed that p20 protein, a viral suppressor of RNA silencing (VSR) encoded by citrus tristeza virus (CTV), mediated autophagic degradation of SUPPRESSOR OF GENE SILENCING 3 (SGS3), a plant-specific RNA-binding protein that is pivotal in antiviral RNA silencing. CTV infection activated autophagy, and the overexpression of p20 was sufficient to induce autophagy. Silencing of autophagy-related genes NbATG5 and NbATG7 attenuated CTV infection in Nicotiana benthamiana plants. In contrast, knockdown of the autophagy negative-regulated genes NbGAPCs led to virus accumulation, indicating the proviral role of autophagy in CTV infection. Further investigation found that p20 interacted with autophagy-related protein ATG8 through two ATG8-interacting motifs (AIMs) and sequestered SGS3 into autophagosomes by forming the ATG8-p20-SGS3 ternary complex. The mutations of the two AIMs in p20 (p20mAIM1 and p20mAIM5) abolished the interaction of p20 with ATG8, resulting in the deficiency of autophagy induction, SGS3 degradation, and VSR activity. Consistently, N. benthamiana plants infected with mutated CTVmAIM1 and CTVmAIM5 showed milder symptoms and decreased viral accumulation. Taken together, this study uncovers the molecular mechanism underlying how a VSR mediates the interplay between RNA silencing and autophagy to enhance the infection of a closterovirus.